Prevention of Depression in Patients with Cancer: A Systematic Review - Sari, Yulia Indah Permata; Sukartini, Tintin; Yunitasari, Esti (International Journal of Psychosocial Rehabilitation, 2020)
Depression and depressive symptoms are prevalent in patients with cancer. Depression is under- diagnosed and therefore the patients often receive inadequate treatment for their depression. The aim of this study was to identify ways to prevent depression in patients with cancer. This systematic review used the Preferred Reporting Items for Systematic Review (PRISMA) approach. Databases were used to identify suitable articles from Scopus, PubMed, Science Direct and Proquest. The articles were limited to being published between 2009 and 2020, written in English and full-text articles. The literature review used the keywords “anxiety, antidepressant, cancer, depression and preventive.” When searching the articles, “AND” was also used. The inclusion criteria in the search strategy consisted of: 1) adult humans ≥18 years of age diagnosed with cancer; 2) undergoing antidepressive treatment of any kind; 3) depression and/or depressive symptoms and 4) the study design was a randomized controlled trial. Studies were excluded if the studies had less than 30 samples as this means that they do not have enough strength to use to detect a significant relationship. Following this screening, 15 articles met the inclusion criteria. The studies were classified into 3 groups based on the type of intervention used. The interventions were pharmacotherapy, psychotherapy and other interventions such as exercise programs. Depression in patients with cancer can be prevented. Preventive treatment should start before or during the oncological treatment. Treating psychiatric conditions in patients with cancer may improve not only their quality of life and prognosis but also their survival.